2009
DOI: 10.2478/10004-1254-60-2009-1896
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cytogenetic Status of Human Lymphocytes After Exposure to a High Concentration of Bee Venom In Vitro

Abstract: Several studies have reported radioprotective, antimutagenic, anti-infl ammatory, antinociceptive, and anticancer effects of bee venom both in the cell and the whole organism. The aim of this study was to assess the effects of a single high dose of 100 µg mL -1 of whole bee venom in human lymphocytes in vitro over a variety of time spans (from 10 min to 24 h). After the treatment, we used the comet assay and micronucleus test to see the effect of bee venom on the cell. The comet assay confi rmed that the venom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…These contradictory results are attributed to variability in the chemical composition of the preparations of CHL used, concentration and source of CHL, as well as to the experimental model (in vivo or in vitro) (Chernomorsky et al, 1997;Tumolo & Lanfer-Marquez, 2012). Therefore, to establish the toxicological profile of CHL, we assessed its cytotoxicity and genotoxicity on HPBLs using widely accepted biomarkers for the evaluation of genome damage after exposure to different physical and/or chemical agents as well as to a wide range of natural products (Garaj-Vrhovac & Gajski, 2009). We found that CHL in the concentration range tested (0.1-100 lg/ml) was not cytotoxic and genotoxic to HPBLs.…”
Section: Discussionmentioning
confidence: 98%
“…These contradictory results are attributed to variability in the chemical composition of the preparations of CHL used, concentration and source of CHL, as well as to the experimental model (in vivo or in vitro) (Chernomorsky et al, 1997;Tumolo & Lanfer-Marquez, 2012). Therefore, to establish the toxicological profile of CHL, we assessed its cytotoxicity and genotoxicity on HPBLs using widely accepted biomarkers for the evaluation of genome damage after exposure to different physical and/or chemical agents as well as to a wide range of natural products (Garaj-Vrhovac & Gajski, 2009). We found that CHL in the concentration range tested (0.1-100 lg/ml) was not cytotoxic and genotoxic to HPBLs.…”
Section: Discussionmentioning
confidence: 98%
“…However, Kim et al [40] noted that the viability of an uninjured mouse hepatocyte cell line treated with BV did not change significantly, although this was most likely due to the minute concentration used (10 ng/mL). Similarly, Garaj-Vrhovac and Gajski [41] declared that high concentrations of BV (100  μ g/mL) led to cellular instability in human lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Clastogenic and aneugenic effects of bee venom were noticed in our previous report assessing cytogenotoxic effects of bee venom by virtue of measuring frequency of micronuclei, nucleoplasmic bridges and nuclear buds as micronucleus test parameters. [20] In this study, significantly elevated frequency of SCE was recorded in all of the exposed samples and this increase was time and dose dependent. Besides, the average number of HFC in treated samples as indicator of highly damaged DNA was even higher in compare to the unexposed ones.…”
Section: Resultsmentioning
confidence: 91%
“…[1,3,4,6,37] However, there are not many studies regarding its potential DNA damaging effect that could be helpful when assessing its therapeutic values. [20,38,39] In this study evaluation of DNA damage was made by virtue of measuring frequency of SCE in addition to determination of lymphocyte viability. Because of the differential staining, SCE technique also allows metaphases in first division, second division, and third division to be recognized after culturing.…”
Section: Resultsmentioning
confidence: 99%